2019
DOI: 10.1016/j.neuron.2019.01.037
|View full text |Cite
|
Sign up to set email alerts
|

A Visual Circuit Related to Habenula Underlies the Antidepressive Effects of Light Therapy

Abstract: Light plays a pivotal role in the regulation of affective behaviors. However, the precise circuits that mediate the impact of light on depressivelike behaviors are not well understood. Here, we show that light influences depressive-like behaviors through a disynaptic circuit linking the retina and the lateral habenula (LHb). Specifically, M4type melanopsin-expressing retinal ganglion cells (RGCs) innervate GABA neurons in the thalamic ventral lateral geniculate nucleus and intergeniculate leaflet (vLGN/IGL), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
195
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(216 citation statements)
references
References 58 publications
10
195
0
1
Order By: Relevance
“…When these inputs are removed before a critical time window, zebrafish dHb loses it functional lateralization (Dreosti et al, 2014). Our observations are also in line with the lack of evidence for the functional lateralization in the mammalian habenula, where most studies focus on the lateral habenula (Huang et al, 2019). Hence, the ontogeny of zebrafish habenular function might follow the phylogeny of vertebrate habenula evolution.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…When these inputs are removed before a critical time window, zebrafish dHb loses it functional lateralization (Dreosti et al, 2014). Our observations are also in line with the lack of evidence for the functional lateralization in the mammalian habenula, where most studies focus on the lateral habenula (Huang et al, 2019). Hence, the ontogeny of zebrafish habenular function might follow the phylogeny of vertebrate habenula evolution.…”
Section: Discussionsupporting
confidence: 80%
“…The habenula is a particularly interesting brain region, as it was shown to integrate both sensory Miyasaka et al, 2009;Zhang et al, 2017) and cortico-limbic inputs (Herkenham and Nauta, 1977;Hong et al, 2011;Lazaridis et al, 2019;Matsumoto and Hikosaka, 2007;Meye et al, 2016;Okamoto et al, 2012;Stamatakis et al, 2013;Turner et al, 2016;Warden et al, 2012) while directly regulating the function of monoaminergic brain nuclei controlling behaviour (Duboue et al, 2017;Flanigan et al, 2017;Hikosaka, 2010;Krishnan et al, 2014;Lin and Jesuthasan, 2017;Matsumoto and Hikosaka, 2007;Zhang et al, 2017). Dysfunction of the habenula is also shown to be associated with several neurological conditions and mood disorders including depression (Huang et al, 2019;. The habenula is composed of several subdomains or modules based on its neurochemical profiles deCarvalho et al, 2014;Pandey et al, 2018;Ren et al, 2011;Seigneur et al, 2018;Viswanath et al, 2013), anatomical projections (Agetsuma et al, 2010;Amo et al, 2010;Amo et al, 2014;Lee et al, 2010), and the activity of habenular neurons (Amo et al, 2014;Dreosti et al, 2014;Jetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While the central projections of the ipRGCs have not been described in Arvichanthis ansorgei, previous work has been done in diurnal rodents from the same genus: Arvicanthis niloticus (Langel et al 2015). The results of that study pointed out that the main characteristics of these cells are fundamentally the same as those described in nocturnal rodents (Hannibal and Fahrenkrug 2004;Hattar et al 2006;Reifler et al 2015). Thus, among the areas that are innervated by the ipRGCs are the SCN, the intergeniculate leaflet (IGL), and presumably the lateral hypothalamus (LH).…”
Section: Groupsmentioning
confidence: 95%
“…Previous studies have revealed the existence of intrinsically photosensitive retinal ganglion cells (ipRGCs) that express the photopigment melanopsin (with a peak spectrum of absorption at k = 480 nm, i.e., blue light), in addition to rods and cones. The anatomical projections of the ipRGCs directly reach the hypothalamic suprachiasmatic nucleus (SCN), the site of the main circadian clock, and other parts of the brain involved in energy metabolism, glucose homeostasis, reward and food intake (Provencio et al 2000;Hattar et al 2006;LeGates et al 2014). Combined with the evidence that ALAN is a risk factor for metabolic diseases, this leads to the hypothesis that ALAN can alter food intake and glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, this makes the LHb an intriguing target for novel antidepressant therapies (Cui et al, 2018; Lecca et al, 2016; Li et al, 2011; Sartorius et al, 2010; Schneider et al, 2013; Winter et al, 2011; Yang et al, 2018). Notably, multiple studies have shown that potentiation of inhibition within the LHb yields an antidepressant effect (Huang et al, 2019; Lecca et al, 2016; Tchenio et al, 2017; Winter et al, 2011), likely by disinhibition of the reward circuitry. Despite this, however, the neural circuitry which mediates inhibitory signalling within the LHb is not well understood.…”
Section: Introductionmentioning
confidence: 99%